The Influence Of Job Training and Job Stress on Employee Performance at PT. Muhyi Bazana Putra - Joevito Rizky Rulif; Syahrum Agung; Anuraga Kusumah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In research entitled the influence of Job Training and Job Stress on employee performance, the number of samples taken was 53 PT respondents. Muhyi Bazana Putra, Depok City. The method used is a questionnaire research instrument distributed to employees processed using the SPSS version 25 application. This research was carried out at PT. Muhyi Bazana Putra, Depok City. The variables Job Training (X1) and Job Stress (X2) on employee performance (Y) are processed using correlation analysis, regression analysis, t test, f test and coefficient of determination. The results of this research show that the Job Training variable (X1) has a significant and positive effect on employee performance (Y), the Job Stress variable (X2) has a significant and negative effect on employee performance (Y). Simultaneously Job Training (X1) and Job Stress (X2) have a significant and positive effect on employee performance (Y) PT. Muhyi Bazana Putra, Depok City.